Pengaruh Pengendalian Internal, Manajemen Risiko Dan Wistleblowing System Terhadap Pencegahan Fraud - Agus Sulistiyo; Harti Budi Yanti (Jurnal Akuntansi dan Pajak, 2022)
This study aims to examine the effect of internal control, risk management and whistleblowing system on fraud prevention. This research is a type of quantitative research, the data used in this study are primary data obtained from questionnaires, the number of samples is 35 respondents using purposive sampling technique. The data analysis technique used multiple linear regression with SPSS v24 program tools. The results showed that internal control had a significant effect on fraud prevention. Risk management has a significant effect on fraud prevention and the whistleblowing system has a significant effect on fraud prevention. Simultaneously internal control, risk management and whistleblowing system has a significant effect on fraud prevention.